Ease: An Environment for Architecture Study and Experimentation - Whalley, David; Davidson, Jack (University of Virginia, Department of Computer Science, 1989)
Obtaining accurate and meaningful measurements of the execution behavior of instruction set architectures is difficult. Measurement systems often impose a heavy performance penalty that limits the types of programs that can be used. Furthermore, meaningful measurements can only be obtained if realistic (not toy) benchmark programs are used. Such programs, however, requires high-level language compilers to translate the benchmarks to machine code. The problem is further complicated as most machines require "optimizing" compilers in order for their capabilities to be fully exploited. This paper describes an environment that provides these capabilities. It allows detailed measurements of the execution behavior of realistic programs to be generated without incurring a heavy performance penalty. The accompanying compiler technology allows optimizing compilers to he built that fully exploit the capabilities of the machine. To illustrate the power of the environment, its use in a number of applications is described. Note: Abstract extracted from PDF file via OCR
Original submission date: 2013-10-11T19:49:27Z